The effects of resistance exercise on cognitive function, amyloidogenesis, and neuroinflammation in Alzheimer’s disease - Azevedo, Caroline Vieira; Hashiguchi, Debora; Campos, Henrique Correia; Figueiredo, Emilly V.; Otaviano, Sthefanie Ferreira S. D.; Penitente, Arlete Rita; Arida, Ricardo Mario; Longo, Beatriz Monteiro (Frontiers in Neuroscience, 2023)
With the increasing prevalence of Alzheimer’s disease (AD) and difficulties in finding effective treatments, it is essential to discover alternative therapies through new approaches. In this regard, non-pharmacological therapies, such as physical exercise, have been proposed and explored for the treatment of AD. Recent studies have suggested that resistance exercise (RE) is an effective strategy for promoting benefits in memory and cognitive function, producing neuroprotective and anti-inflammatory effects, and reducing amyloid load and plaques, thereby reducing the risk, and alleviating the neurodegeneration process of AD and other types of dementia in the elderly. In addition, RE is the exercise recommended by the World Health Organization for the elderly due to its benefits in improving muscle strength and balance, and increasing autonomy and functional capacity, favoring improvements in the quality of life of the elderly population, who is more likely to develop AD and other types of dementia. In this mini-review, we discuss the impact of RE on humans affected by MCI and AD, and animal models of AD, and summarize the main findings regarding the effects of RE program on memory and cognitive functions, neurotrophic factors, Aβ deposition and plaque formation, as well as on neuroinflammation. Overall, the present review provides clinical and preclinical evidence that RE plays a role in alleviating AD symptoms and may help to understand the therapeutic potential of RE, thereby continuing the advances in AD therapies.